2022
DOI: 10.12659/msm.938867
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bond Strength of Orthodontic Brackets Onto the Tooth Enamel of 120 Freshly Extracted Adult Bovine Medial Lower Incisors Using 4 Adhesives: A Resin-Modified Glass Ionomer Adhesive, a Composite Adhesive, a Liquid Composite Adhesive, and a One-Step Light-Cured Adhesive

Abstract: Background This study aimed to compare the bond strength of orthodontic brackets onto the tooth enamel of 120 freshly extracted adult bovine medial lower incisors using 4 adhesives: a resin-modified glass ionomer adhesive, a composite adhesive, a liquid composite adhesive, and a one-step light-cured adhesive. Material/Methods The study group (120 freshly extracted bovine medial lower incisors) was divided into equal subgroups depending on the type of adhesive used to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
4
2
Order By: Relevance
“…Group 6 (TSEP + TXT) obtained a significantly lower SBS value (19.38 MPa) than Groups 2 and 3. These results contradicted some studies in which SBS values were similar or higher for a primer/composite resin combination relative to FUJI [ 6 , 27 29 ]. Study results differ depending on the pretreatment applied, the localization of bonding (palatal or vestibular enamel) or the addition of thermocycling to simulate intraoral aging [ 6 , 28 , 29 ].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Group 6 (TSEP + TXT) obtained a significantly lower SBS value (19.38 MPa) than Groups 2 and 3. These results contradicted some studies in which SBS values were similar or higher for a primer/composite resin combination relative to FUJI [ 6 , 27 29 ]. Study results differ depending on the pretreatment applied, the localization of bonding (palatal or vestibular enamel) or the addition of thermocycling to simulate intraoral aging [ 6 , 28 , 29 ].…”
Section: Discussioncontrasting
confidence: 91%
“…In contrast, some scholars found higher SBS values for FUJI than for composite resins, which agreed with our results [ 31 , 32 ]. Indeed, Althagafi [ 27 ] showed higher SBS values for FUJI (25.2 MPa) than for TXT (20.9 MPa), regardless of the protocol used (prior enamel etching, application of fluoride gel, bonding to healthy or eroded enamel). Authors explained their results by the improved polymerization of FUJI under the brackets [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This nding suggested that it was relatively easy to clean the adhesive after debonding and that there was a greater risk of enamel fracture during bracket debonding when using a universal adhesive than when using a self-etching primer. Several authors reported a greater risk of enamel fracture during debonding for composite resins than for RMGICs, 22,38,39 for which failure occurred preferentially at the RMGIC/bracket interface or within the material with an RMGIC. There was generally additional adhesive remaining on the tooth at debonding and a reduced risk of enamel fracture.…”
Section: Failure Modesmentioning
confidence: 99%
“…19,20 However, although many authors support the use of RMGICs for bonding orthodontic brackets, the data in the literature remain controversial, with some scholars reporting more insu cient adhesion values, more frequent debonding and greater mechanical wear than with the use of a primer/composite resin combination. [22][23][24] The aims of this in vitro study are to assess whether Riva LC HV (SDI), which is a restorative RMGIC, can be a competitor to either Fuji Ortho LC or the adhesive/Transbond XT combination (3M Unitek) for bonding orthodontic attachments to enamel and to determine which bonding protocol(s) can optimize their adhesion values.…”
Section: Introductionmentioning
confidence: 99%
“…The resin modified glass ionomer cement (RMGIC) releases fluoride and prevents enamel demineralization [10]. However, studies have shown significantly lower bond strengths of the RMGIC when compared to the resin composite in orthodontics [11,12]. The RMGIC Fuji Ortho LC (GC Corporation, Tokyo, Japan) has shown upgraded bond strength when used on etched and dried enamel [13].…”
Section: Introductionmentioning
confidence: 99%